Twenty-four position tilt test for accelerometer cross-axial sensitivity compensation - Malović, Miodrag Z.; Brajović Ljiljanа М.; Šekara, Tomislav B. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Cross-axial or transverse sensitivity of an accelerometer can be compensated by digital processing of the output signal. To perform this, it is necessary to determine coefficients that describe a sensor’s response to excitation experimentally. Many procedures advised by standards and scientific papers use expensive equipment which is not available in every laboratory. Therefore, a simple method is proposed, namely a variation of the static tilt test, requiring no other measuring equipment than the sensor itself and a flat surface. Results vary depending on sensor surface and housing quality, but it has been shown that cross sensitivity effects can be reduced from several percent usually associated with commercial three-axial MEMS accelerometers down to 1% or less.